Organizational development patterns and regularities during implementation of change management strategies. (Journal of Economic Research & Business Administration, 2015)
The article stresses the importance of change efforts in contemporary organizations and therefore the need for change has been explicitly expressed and stated. The defi nitions of change and change management are provided with the aim to identify their essence and role. The article is also about knowing change patters and regularities during implementation of various strategies of change by managers in modern organizations. Change patterns are laws and regularities that characterize the fl ow and state of any change being made in an organization. Additionally, several change management strategies are described and their impact degree is identifi ed.
Keywords: change management; organizational changes; organizational development patterns and regularities; change management strategies